Military and Political Influence on the Portfolio of Global Reserve Currencies - M. Y. Alekseev; P. A. Kolyandra; B. M. Cheskidov (Финансы: теория и практика)
This paper analyses a new concept presented in the works of B. Eichengreen, A.J. Mehl, L. Chitu “Mars or Mercury? The Geopolitics of International Currency Choice”, according to which the state’s possession of nuclear weapons is linked to its possession of reserve currency. The paper aims to provide a detailed assessment of how gaining reserve currency status depends on the military and political potential of the state issuer. The research method is an analysis of the historical material and the current state of the issue under discussion. The study shows the relationship between the global military and political leadership and control over the global financial infrastructure, which increases its importance as a space for interstate conflicts. It has been proven that neither the presence of military power nor the ability and willingness to provide partners with security guarantees do not predetermine the acquisition of the reserve status by the national currency. This status is acquired as a result of control over global investment processes, in the implementation of which military power plays a significant, but not exclusive role. This power, as the potential for economic and financial dominance, is a derivative of the scale and level of development of the national economy, with a key factor in its deep involvement in international trade. From the point of view of practical forecasting of economic, military and political development, the authors conclude that in the foreseeable future, despite the strengthening of its military potential, the PRC will not be able and, most likely, will not try to obtain the status of the yuan as a reserve currency. The United States, in turn, will increasingly use its dominance in the capital market and control over the global financial infrastructure as a tool to maintain global leadership. Further study of the considered issues will significantly increase the efficiency of forecasting economic processes in relation to the military and political situation.